Perubahan dalam Perilaku Sosial Masyarakat Kampung Adat Kuta Menghadapi Era Modernisasi - Ayu Anindia; Ferina Dyah Prastiyanti; Desi Purwaningsih (Jurnal Hukum, Administrasi Publik dan Negara, 2024)
Changes in the social behavior of the Kuta Traditional Village community are becoming increasingly significant along with the impact of the ongoing modernization era. Kuta Traditional Village, a community rich in traditions and cultural values, is experiencing transformation in various aspects of their daily lives. This study explores how modernization affects the social behavior patterns of the Kuta Traditional Village community, from traditions to their social interactions. Through an in-depth qualitative approach, the results of this research describe the dynamics of social change occurring in this traditional village and seek an understanding of how they adapt to the ever-evolving modern era.